2007
DOI: 10.1074/jbc.m702390200
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate (EGCG), A Green Tea Polyphenol, Suppresses Hepatic Gluconeogenesis through 5′-AMP-activated Protein Kinase

Abstract: Epigallocatechin-3-gallate (EGCG), a main catechin of green tea, has been suggested to inhibit hepatic gluconeogenesis. However, the exact role and related mechanism have not been established. In this study, we examined the role of EGCG in hepatic gluconeogenesis at concentrations that are reachable by ingestion of pure EGCG or green tea, and are not toxic to hepatocytes. Our results show in isolated hepatocytes that EGCG at relatively low concentrations (<1 M) inhibited glucose production via gluconeogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
228
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 305 publications
(248 citation statements)
references
References 51 publications
(43 reference statements)
17
228
3
Order By: Relevance
“…Various natural molecules found in the human diet have been described as potential 4 agents to treat diabetes and hyperlipidemia [11][12][13][14]. Furthermore, recent studies have shown that some of these compounds strongly stimulate hepatic AMPK [11][12][13], an action that may help to explain some of the antihyperlipidemic effects of these natural derivatives and that provides an avenue for ameliorating hyperlipidemia and accelerated atherosclerosis in diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Various natural molecules found in the human diet have been described as potential 4 agents to treat diabetes and hyperlipidemia [11][12][13][14]. Furthermore, recent studies have shown that some of these compounds strongly stimulate hepatic AMPK [11][12][13], an action that may help to explain some of the antihyperlipidemic effects of these natural derivatives and that provides an avenue for ameliorating hyperlipidemia and accelerated atherosclerosis in diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products have played a significant role in new drug discovery and development processes [16], with some reported to possess glucose-lowering effects [17,18]. Moreover, natural products such as alkaloids, bitter melon extracts and epigallocatechin-3-gallate (EGCG) have been found to activate AMPK and improve metabolic disease [17,19]. However, most of these agents displayed inadequate efficacy in vivo, leading to the demand to develop more effective AMPK activators.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not report whether green tea extract alone enhanced endurance. Green tea catechins can activate AMPK in non-muscle cells [90,91], suggesting a mechanism similar to other AMPK activators such as AICAR [55] and resveratrol [50]. However, Murase et al [89] suggest that the actions of green tea extract in skeletal muscle are independent of PPARα/δ signalling, which contrasts with the purported mechanism of AICAR treatment [55].…”
Section: Pgc-1αmentioning
confidence: 86%